ANALISIS PENERAPAN TEKNIK MEMBACA SEKILAS (SKIMMING) TERHADAP PEMAHAMAN MEMBACA SOAL CERITA MATEMATIKA SISWA KELAS V A SD NEGERI BIBISLUHUR I - Wiryastuti, Virliana Mareta; Prihastari, Ema Butsi; Mustofa, Mukhlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the application of the skimming technique to the reading comprehension of mathematical word problems among Class V A students at SD Negeri Bibisluhur I. The main focus of this research is to examine how the skimming technique is implemented and to what extent it can improve students' understanding in solving mathematical word problems. This research employed a qualitative approach with data collection techniques including observation, documentation, and interviews with the principal, homeroom teacher, and students. The research subjects consisted of five students out of a total of twenty-four students in Class V A. The results showed that the application of the skimming technique helped students identify important information in the problems, such as key words and relevant numbers. Students were able to understand what was known and what was being asked more quickly, which led to more structured problem-solving steps. Additionally, this technique improved reading efficiency and reduced errors caused by irrelevant information. Although some students in the lower category were not yet fully accurate in solving the problems, they still demonstrated initial development in understanding the structure of the questions. Overall, the skimming technique had a positive impact on students' reading comprehension and problem-solving abilities in mathematical word problems.